Using Metaphors To Reduce The Uncertainty In Play Therapy Room - Tribuana Tungga Dewi (Universitas Prof. Dr. Moestopo (Beragama), 2024)
This article aims to describe how the strategy of reducing uncertainty occurs in the play therapy room. As a method in psychotherapy, a play and creative arts therapist must be able to establish a good relationship with the client so that the client feels safe and comfortable during the therapy process. To establish a safe and comfortable relationship, a process of reducing uncertainty is needed between the therapist and client when communicating in the therapy room. Berger and Calabrese consider that reducing uncertainty will result in self-disclosure which can strengthen the source-receiver relationship in the communication process. After conducting observation in Client ANA’s case for 24 sessions, it is found that in play therapy, the reduction of uncertainty occurred uniquely by using various metaphors chosen by the client independently. In ANA's case, the uncertainty reduction strategy started with an active strategy, followed by simultaneous use of passive and interactive strategies.